Study on the relationship between the changes in polyamine content and seedless grapes embryo rescue breeding - Li, Guirong; Li, Kaiwei; Han, Feifei; Gao, Huanchao; Wang, Ling (Frontiers in Plant Science, 2024)
Four ovules of 4 naturally pollinated Eurasian seedless grape cultivars, including ‘Thompson Seedless’ grape (hereinafter referred to as ‘Seedless White’ grape), ‘Flame Seedless’ grape, ‘Heshi Seedless’ grape and ‘Ruby Seedless’ grape were employed for the study. Changes in the endogenous polyamine content, exogenous polyamine content, and the suitable combination of exogenous polyamines in the seedless grape berries and isolated ovules were determined during the best embryo rescue period. Furthermore, the effect of different exogenous polyamine contents on the germination and seedling rate of different seedless grape embryos was analyzed. In the best embryo rescue period, the number of ovules had different effects on the content of polyamines. For seedless grape cultivars with 4 ovules, a high content of polyamines was found to be more beneficial in the embryonic development. The existence of embryos had different effects on the development of embryos. In the ovules with embryo, an increase in the content of polyamine was beneficial to the growth and development of the ovule. Different ratios of exogenous polyamines had varying effects on the embryonic development. Putrescine (Put) exhibited the greatest effect on the embryonic development. Further, correlation analysis showed that different combinations of exogenous polyamines had varying effects on the embryonic development. A maximal ovule development was observed in the combination of exogenous polyamines of putrescine2+spermidine2+spermine1. For maximal embryo germination and seeding formation, the optimal combination was putrescine2+spermidine2+spermine2. Irrespective to the number of ovules or the existence of embryos, the results indicated that a high content of endogenous polyamines promoted the growth and development of embryos. The embryo rescue efficiency of different exogenous polyamines was different, and the appropriate combination of exogenous polyamines was beneficial to the growth and development of ovules, with a high development rate of the ovule and seedling.